Glutamine dipeptide-supplemented parenteral nutrition improves the clinical outcomes of critically ill patients: a systematic evaluation of randomised controlled trials - Stehle, Peter; Kojic, Dubravka (e-SPEN journal, 2017)
Background & aims: Early randomised controlled trials (RCTs) testing whether parenteral nutrition regimens that include glutamine dipeptides improves the outcomes of critically ill patients demonstrated convincingly that this regimen associates with reduced mortality, infections, and hospital stays. However, several new RCTs on the same question challenged this. To resolve this controversy, the present meta-analysis was performed. Stringent eligibility criteria were used to select only those RCTs that tested the outcomes of critically ill adult patients without hepatic and/or renal failure who were haemodynamically and metabolically stabilised and who were administered glutamine dipeptide strictly according to current clinical guidelines (via the parenteral route at 0.3-0.5 g/kg/day; max. 30% of the prescribed nitrogen supply) in combination with adequate nutrition. Methods: The literature research (PubMed, Embase, Cochrane Central Register of Controlled Trials) searched for English and German articles that had been published in peer-review journals (last entry March 31, 2015) and reported the results of RCTs in critically ill adult patients (major surgery, trauma, infection, or organ failure) who received parenteral glutamine dipeptide as part of an isoenergetic and isonitrogenous nutrition therapy. The following data were extracted: infectious complications, lengths of stay (LOS) in the hospital and intensive care unit (ICU), duration of mechanical ventilation, days on inotropic support, and ICU and hospital mortality rates. The selection of and data extraction from studies were performed by two independent reviewers. Results: Fifteen RCTs (16 publications) fulfilled all selection criteria. They involved 842 critically ill patients. None had renal and/or hepatic failure. The average study quality (Jadad score: 3.8 points) was well above the predefined cut-off of 3.0. Common effect estimates indicated that parenteral glutamine dipeptide supplementation significantly reduced infectious complications (relative risk [RR] = 0.70, 95% CI 0.60, 0.83, p < 0.0001), ICU LOS (common mean difference [MD] −1.61 days, 95% CI −3.17, −0.05, p = 0.04), hospital LOS (MD −2.30 days, 95% CI −4.14, −0.45, p = 0.01), and mechanical ventilation duration (MD −1.56 days, 95% CI −2.88, −0.24, p = 0.02). It also lowered the hospital mortality rate by 45% (RR = 0.55, 95% CI 0.32, 0.94, p = 0.03) but had no effect on ICU mortality. Visual inspection of funnel plots did not reveal any potential selective reporting of studies. Conclusions: This meta-analysis clearly confirms that when critically ill patients are supplemented with parenteral glutamine dipeptide according to clinical guidelines as part of a balanced nutrition regimen, it significantly reduces hospital mortality, infectious complication rates, and hospital LOS. The latter two effects indicate that glutamine dipeptide supplementation also confers economic benefits in this setting. The present analysis indicates the importance of delivering glutamine dipeptides together with adequate parenteral energy and nitrogen so that the administered glutamine serves as precursor in various biosynthetic pathways rather than simply as a fuel.